Consumption of Caffeine and Sleeping Habit among University Students. - Lukman@Zawawi, Mohamad; Azlini, Chik; Normala, Riza (2018)
This study is intended to find out the relationship between the consumption of caffeine towards the changing in sleeping habit among university students.This study utilizes the quantitative method in a descriptive form where 311 samplings need to answer the questionnaire. The 311 samplings have consisted of Universiti Sultan Zainal Abidin students. The students involved representatives from three campuses which are Campus Gong Badak, Campus Besut, and City Campus. This study uses 18 items a questionnaire that is comprised of three parts namely the demographics of the respondent, the frequency of the caffeine consumption and sleeping pattern. Later, the collected data will be analyzed by using Exploration Analysis. Then, the researcher will transfer the data into the Excel spreadsheet for the transparency of the data and later will be analyzed.The result of this study shows that the consumption of caffeine drunk in the evening is the highest with 70.42% and causes 59.81% in the sleeping pattern disorder among the respondents. Furthermore, the results also indicate that completing the task with 96.46% is the main reason the students need to sleep late. Hence, the usage of caffeine drunk during nighttime will affect ones’ sleeping pattern.